Perancangan Sistem Penjualan Furniture Pada UD Usaha Jaya Mandiri Berbasis Website - Anthony Anthony; Zyad Rusdi; Wasino Wasino (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
UD Usaha Jaya Mandiri is a shop in the City of Tanjung Pinang which is engaged in selling furniture. Seeing the progress of the development of Science and Technology today, the demands on the development of sales and existence in the company must be increased, one way is to create a website, because in this way the UD Usaha Jaya Mandiri company engaged in the sale of furniture can be better known by the public broad, and can increase sales at UD Usaha Jaya Mandiri Company. The method used to obtain data requirements is the method of observation and interview methods. The software system design method used is System Development Life Cycle (SDLC) and the programming language used to create programs is PHP and to manage the database it uses PhpMyAdmin. The results of this application program have a shopping cart feature which is a very useful feature, because it makes it easier for customers to order and make purchases in stores, and this application program can provide information on sales and order reports.